1995
DOI: 10.1242/jcs.108.8.2825
|View full text |Cite
|
Sign up to set email alerts
|

An anti-αv-integrin antibody that blocks integrin function inhibits the development of a human melanoma in nude mice

Abstract: A series of murine monoclonal antibodies were raised against purified human alpha v beta 3 integrin and against M21 human melanoma cells. Five notable hybridomas were identified by ELISA on purified integrins, and the isolated antibodies bound the alpha v-chain. These antibodies, 17E6, 20A9, 23G5, 14D9.F8 and 10G2, recognised the extracellular domains of the integrin, and were shown to be reactive in FACS, immunoprecipitation, ELISA, and ELISA on fixed cells with M21, M21-L4, and UCLA-P3, but not with the alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(31 citation statements)
references
References 72 publications
1
28
0
Order By: Relevance
“…The improvement in the uptake of peptide-decorated NPs by the B16F10 cell line is in agreement with the cytotoxicity data obtained by the MTT assay. This strongly supports that adsorption/uptake is determined by αvβ3 integrin binding mediated by the RGD sequence. , RGD-like peptides have the highest affinity for αvβ3 integrin, but they are able to bind the αvβ5 and α5β1 integrins as well, which can contribute to NP binding. , …”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The improvement in the uptake of peptide-decorated NPs by the B16F10 cell line is in agreement with the cytotoxicity data obtained by the MTT assay. This strongly supports that adsorption/uptake is determined by αvβ3 integrin binding mediated by the RGD sequence. , RGD-like peptides have the highest affinity for αvβ3 integrin, but they are able to bind the αvβ5 and α5β1 integrins as well, which can contribute to NP binding. , …”
Section: Discussionsupporting
confidence: 68%
“…This strongly supports that adsorption/uptake is determined by αvβ3 integrin binding mediated by the RGD sequence. 66,67 RGD-like peptides have the highest affinity for αvβ3 integrin, but they are able to bind the αvβ5 and α5β1 integrins as well, which can contribute to NP binding. 68,69 The three different NP formulations probably take advantage of different pathways to gain access to the cytoplasmic component.…”
Section: ■ Discussionmentioning
confidence: 99%
“…74 It has indeed been shown that micelles slightly surface modified by antibodies accumulated in tumors, showing a better anti-tumor efficacy. 158 Antibodies-decorated nanoparticulate systems have been employed in the field of cancer (anti-CD3 Mab, 159 anti-HER2 Mab (also called trastuzumab or Herceptin), 160 EGFRMab, 161 DI17E6 Mab, 162 anti FAS Mab, 163 anti antigen rich breast cancer cells Mab, 164 AMB8LK Mab, 165 anti-CD20 mAB, 166 anti-CEA Mab 167 ), Alzheimer's disease (anti-Ab 1-42 MAb), 168 brain delivery (29B4, 169 OX26, 170 R17217, 171 anti-CD44 mAB, 172 anti-NCAM1 Mab 173 ) and autoimmune diseases (anti CD4 + ). 174 A specific target to inflamed endothelium (generally observed in various pathological settings such as cancer, cardiovascular disease and arthritis) which is characterized by overexpression of endothelial cell adhesion molecules, was achieved using anti-ICAM-1 Mab, anti VCAM-1 Mab, anti E-selectin Mab as well as anti P-selectin Mab.…”
Section: Ligands Employed For Targeted Deliverymentioning
confidence: 99%
“…Cytoskeleton components (e.g., F-actin) and mechanosensitive signaling factors such as FAK and Cdc42 are known to be involved in the response of living cells to mechanical stimulations. 17,36 Immunofluorescence staining showed that the expressions of these components decreased on the substrates with increasing tether mobility (MNP2−20k−M) (Figure 2a). In contrast, cells cultured on the substrate with low/magnetically restricted ligand tether mobility (MNP2− 20k+M) showed robust expression of these mechanotransduction markers.…”
Section: ■ Results and Discussionmentioning
confidence: 99%